2017
DOI: 10.1021/acs.jpcc.7b01798
|View full text |Cite
|
Sign up to set email alerts
|

Antenna-Enhanced Nonlinear Infrared Spectroscopy in Reflection Geometry

Abstract: We propose and demonstrate antenna-enhanced nonlinear infrared (IR) spectroscopy in reflection geometry. Our approach uses resonant metal nanoantennas to enhance near-fields and to amplify the interaction between molecular vibrations and IR light. We successfully obtain amplified nonlinear vibrational signals in backscattering light of nanoantennas using IR pump energy of 10 nJ, with local signal enhancement of more than 7 orders of magnitude. This ultrasensitive and reflection-type method is useful for charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…In the traditional linear SEIRA experiments, the signal scales as a second power of the enhanced electric field . In order to get more insight into the mechanism of plasmon–molecule interaction, we use third-order nonlinear spectroscopy, where the signal scales as the fourth power of the field. Combining the results of linear absorption, third-order femtosecond transient absorption, two-dimensional infrared heterodyned spectroscopy (2DIR), and theoretical analysis, we show that even though locally the plasmon fields are appreciably enhanced, the strength of the near-field coupling is not sufficient to explain the magnitude of the experimentally observed signals in samples with thick polymer films, which we found is caused by the radiation damping interaction. ,, Consequently, we identified that the surface-enhanced signal in samples with a film thickness of only a few nanometers can be dominated by the radiation damping mechanism, especially when strong vibrational chromophores are involved.…”
mentioning
confidence: 99%
“…In the traditional linear SEIRA experiments, the signal scales as a second power of the enhanced electric field . In order to get more insight into the mechanism of plasmon–molecule interaction, we use third-order nonlinear spectroscopy, where the signal scales as the fourth power of the field. Combining the results of linear absorption, third-order femtosecond transient absorption, two-dimensional infrared heterodyned spectroscopy (2DIR), and theoretical analysis, we show that even though locally the plasmon fields are appreciably enhanced, the strength of the near-field coupling is not sufficient to explain the magnitude of the experimentally observed signals in samples with thick polymer films, which we found is caused by the radiation damping interaction. ,, Consequently, we identified that the surface-enhanced signal in samples with a film thickness of only a few nanometers can be dominated by the radiation damping mechanism, especially when strong vibrational chromophores are involved.…”
mentioning
confidence: 99%
“…Here we see that the nonlinear polarization is amplified by a factor of 8 " √ O ̅ (P) 9 P ≡ RM . Equations (5,6) describe that the signal enhancement factors of FL and FNL increase monotonically with each of the nanoantenna polarizability, the coupling strength, and the number of molecules coupled to the nanoantenna.…”
Section: Analytical Formulation and Discussionmentioning
confidence: 99%
“…In this contribution, we demonstrate surface-enhanced ultrafast vibrational spectroscopy by using periodically-arranged IR-resonant nanoantennas, which satisfy the condition near the collective resonance [5,6]. In addition, we analytically formulate the antennaenhancements of molecular vibrational responses with a simple coupled-dipole model ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Their vibration frequencies often appear at near-and mid-infrared spectral region. One promising approach for increase in sensitivity is to amplify the interaction of molecular vibrations with infrared light by using surface plasmon resonance (SPR) enhancement [1]. It becomes possible by interacting the electric field comes from SPR and the polarization associated with the molecular stretching oscillation.…”
Section: Introductionmentioning
confidence: 99%